PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERY ONE IS TEACHER HERE DISERTAI MEDIA POWERPOINT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMAN 8 PADANG TAHUN PELAJARAN 2013/2014 - Indriani, Muthi - (STKIP PGRI Sumbar, 2014)
The low result in biology learning of XI science student in SMAN 8 is caused by some factors, such as the learning process still use conventional method, the students are less active and less motivation in learning, they also tend to be impatient in discussion and depend on to the smarter member in the group. This situation affects to their mark which they get low mark from the minimum passing criteria(KKM). One thing that can be done to encourage students activeness and motivation during learning process is by using active learning strategy type every one is teacher here a long with using power point media. This is a kind of experimental research by using Randomized Control-Group Posttest Only Design. The population of this research is all students of class XI of SMAN 8 Padang in academic year 2013/2014 which consist of five classess. While the sample of this research is the student of class XI science 4 and XI science 5. This research use final tes instrument formed multiple choice test. Based on the results of the test the average mark of the students for experimental class is 78.05 and for control class is 70.27. The analysis results of the test-t that has been done, t count > t table is 3.08 > 1.67. It is means that the hypothesis in this research is accepted so it can be concluded that the result of students learening process in biology class by applying an active learning strategies type of everyone is teacher here a long with Powerpoint media is better than applying conventional learning.